Effects of MHD and wall properties on the peristaltic transport of a Carreau fluid through porous medium - Salih, Dheia; M. Abdulhadi, Ahmed M. Abdulhadi (JOURNAL OF ADVANCES IN PHYSICS, 2014)
This work concerns the peristaltic flow of a Carreau fluid model through porous medium under combined effects of MHD and wall properties. The assumptions of Reynolds number and long wavelength is investigated. The flow is investigated in a wave frame of reference moving with velocity of the wave. The perturbation series in terms of the Weissenberg number (We <1) was used to obtain explicit forms for velocity field and stream function. The effects of thermal conductivity, Grashof number, Darcy number, magnet, rigidity, stiffness of the wall and viscous damping force parameters on velocity, temperature and stream function have been studied.